PENGARUH MEDIA PEMBELAJARAN INTERAKTIF WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS IV MATA PELAJARAN IPAS DI SDS MUHAMMADIYAH 01 PEMATANGSIANTAR - Desya Putri H.RM; Yusra Nasution; Wildansyah Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Wordwall interactive learning tool on the learning outcomes of Year 4 IPAS pupils at SDS Muhammadiyah 01 Pematangsiantar. This is a quantitative study. The research method used was a quasi-experiment. The population consisted of 26 pupils from Year 4 at SDS Muhammadiyah 01 Pematangsiantar. The data collection techniques used were interviews and observation sheets. Based on the research findings and data analysis, the results of the hypothesis test, calculated using the independent samples t-test formula, showed a value of 0.000 < 0.05, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It can therefore be concluded that the interactive learning medium Wordwall has an effect on the learning outcomes of Year 4 pupils at SDS Muhammadiyah 01 Pematangsiantar.